PROTECTIVE EFFECT OF ETHANOLIC ROOT EXTRACT OF COMMIPHORA CAUDATA AGAINST DIABETIC-INDUCED RATS IN HIGH-FAT DIET-STREPTOZOTOCIN MODEL - K, ANITHA; LAKSHMI, SABAPATHI MOHANA; SV, SATYANARAYANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was to explore the phytochemical analysis and antidiabetic potential of the root of Commiphora caudata in high-fat diet (HFD) streptozotocin-induced diabetic rats. Methods: The ethanolic root extract of C. caudata at a dose of 400 mg/kg and 200 mg/kg was administered to diabetic rats. Glibenclamide (5 mg/kg) was used as standard drug. Results: The data were statistically assessed using one-way ANOVA followed by Dennett’s multiple comparison tests. To unfold the mechanism, we studied all the biochemical parameters glucose, total cholesterol, triglycerides (TG), high-density lipoproteins (HDL), low-density lipoproteins (LDL), and very LDL (VLDL) and histopathological examination of the pancreatic tissue section. The ethanolic extracts of root of C. caudata showed significant reduce of the level of cholesterol, TG, LDL, VLDL, and significant increase in the serum level of HDL at 400 mg/kg rather than 200 mg/kg. Conclusion: Further studies should look into the characterization and isolation of the constituents to know the exact mechanism of hypoglycemic activity. Statistical analyses of this screening method confirm that the proposed method is appropriate and it can be expected to improve basic idea to the researcher who is working in area-like antidiabetic activity.